2023
DOI: 10.3389/fmicb.2023.1220042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early postnatal hyperoxia exposure combined with early ovalbumin sensitization on lung inflammation and bacterial flora in a juvenile mouse model of asthma

Abstract: ObjectiveThe aim of this study is to explore the effects of early postnatal hyperoxia exposure combined with early ovalbumin (OVA) sensitization on lung inflammation and bacterial flora in neonatal mice on a juvenile mouse model of asthma.MethodsThirty-two newborn female C57BL/6 J mice were randomly divided into four groups, which including room air+phosphate-buffered saline (PBS) group, hyperoxia+PBS group, room air+OVA group, and hyperoxia+OVA group, according to the hyperoxia exposure and/or OVA induction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…Similar ndings were reported by studies conducted in hospitals and within houses in the UK and Greece, hospitals in Spain, sport centers in Poland and within primary schools in Malaysia [29,33,34]. Despite the different settings and geographical location, the similarity of the common core microbiome could be due to the fact that these bacterial phyla are members the pulmonary micro ora found in many studies [35,36]. A study by Fakunle and team, found that these bacterial phyla were positively associated with lower respiratory tract infections [37] while Fu and their group, found out that the exposure to Actinobacteriota posed a protective effects on the development of childhood asthma [25].…”
Section: Discussionsupporting
confidence: 83%
“…Similar ndings were reported by studies conducted in hospitals and within houses in the UK and Greece, hospitals in Spain, sport centers in Poland and within primary schools in Malaysia [29,33,34]. Despite the different settings and geographical location, the similarity of the common core microbiome could be due to the fact that these bacterial phyla are members the pulmonary micro ora found in many studies [35,36]. A study by Fakunle and team, found that these bacterial phyla were positively associated with lower respiratory tract infections [37] while Fu and their group, found out that the exposure to Actinobacteriota posed a protective effects on the development of childhood asthma [25].…”
Section: Discussionsupporting
confidence: 83%
“…This study is on the basis of previous studies [ 30 ], we will advance the OVA induction to 3 weeks after the birth of mice, modeling at the end of the mouse 6 weeks of age, so the entire modeling procedure was performed at the juvenile stage.…”
Section: Introductionmentioning
confidence: 99%